Tinjauan Kritis atas Sikap Pemerintah Indonesia terhadap Kelompok Kriminal Bersenjata di Papua terhadap Sejumlah Korban Sipil dan Militer (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The Indonesian government has long faced complex armed conflicts, particularly in Papua, involving security forces and Armed Criminal Groups (KKB). This conflict has had a major impact, not only in terms of casualties involving the military and civil society, but also in terms of broader social and political impacts. A more security-oriented approach by the government is often questioned, because on the one hand, it exacerbates human rights violations, creates a negative stigma against the Papuan people, and further limits the space for constructive political dialogue. This ongoing tension has worsened relations between the central government and Papuans, who have long felt marginalized. In addressing these issues, it is important for governments to develop a more holistic approach, by strengthening protection of civil society, increasing transparency and accountability, and opening up space for inclusive dialogue between all relevant parties. A sustainable settlement requires not only security management, but also serious attention to the well-being, rights of the Papuan people, and recognition of their cultural diversity and political aspirations. Going forward, approaches that prioritize dialogue and reconciliation can open up opportunities to achieve a more just and sustainable peace.